An Intervention Study to Increase the Medication Compliance of 60 Years and Older Individuals. (20th October 2021) - Yüksel Güner, M; Kara, M; Kavukcu, N; Çevik, M; Gören, Y; Kocaarslan, D; Şengezer, T; Aslan, D
Abstract: Background: In older age, taking medication at the desired level contributes to the health and well-being, and therefore, constitutes an essential part of the effectiveness of treatment and ultimately desired public health impact and reduced healthcare budgets. However, it is known that medication compliance among older persons is frequently not at a desired level. Therefore, in this study, it was aimed to increase medication compliance through an educational intervention for patients aged 60 and over, who applied to two healthcare facilities in Ankara, Turkey. Methods: This intervention study was implemented in two public health hospitals between March and June 2019. 315 people aged 60 and over participated in the study. The intervention tool was the "teach-back" method. SPSS program was used for data entry and analysis. P value less than 0.05 was indicated for statistical significance. Results: Mean age of the participants was found to be 70.16±7.9 for the control group and 70.27±7.4 for the intervention group. In the intervention group, a statistically significant increase was found in the capacity of learning the long-term benefits of drugs, their side effects and storage conditions, and knowing when the drugs shouldn't be taken, and repeating information about the drugs used (p = 0.000). Conclusions: This study has revealed that medication compliance among older individuals can be increased with an appropriate communication and training method in healthcare settings. Time allocated by health workers in this regard has a potential to respond to the compliance-related needs. With the "Teach-back" method utilized in the interactions between older patients and health workers, it is possible to attain meaningful, large-scale and cost-effective public health outcomes that contribute to the clinical benefits of treatments and the effectiveness of health systems. Key messages: Older people are open to receive information on the actual health needs. A well-structured interaction between healthcare workers and patients involving "teach-back" method contributes to medication compliance among the elderly.